Exploiting metal-free atom transfer radical polymerization for fabrication of styrene-maleic acid polymer-brush grafting chromatographic stationary phase and its separation performances for phospholipids - Yang, Ruilin; Wang, Ping; Guan, Xinhui; Gu, Xiaofei; Qiao, Xiaoqiang (Analytical and bioanalytical chemistry, 2025)
Phospholipids have been considered biomarkers for diagnosing many diseases in recent years. However, the isolation and analysis of phospholipids still face many difficulties. Styrene-maleic acid (SMA) copolymer is currently considered suitable for the separation and analysis of phospholipids due to its ability to enhance and improve the solubility of phospholipid bilayers on cell membranes. In this work, metal-free atom transfer radical polymerization was first exploited to graft SMA copolymer onto the surface of silica gel. With glycerol monolaurate (GML) as the derivatization reagent, Sil-SMA-GML polymer-brush silica-based stationary phase was first developed. The chromatographic retention mechanism revealed that the Sil-SMA-GML column is of hydrophilic/reversed-phase mixed-mode retention modes. The chromatographic separation performance evaluation indicated that the Sil-SMA-GML column had excellent separation capabilities for both hydrophilic and hydrophobic compounds. The maximum column efficiency was up to 78,600 N/m. The Sil-SMA-GML column could also achieve simultaneous separation and analysis of different phospholipid classes and species as well as complex phospholipid extracts from human serum and exosomal phospholipid extracts, demonstrating the good potential of the developed stationary phase.